Case report: Revascularization failure in NF1-related moyamoya syndrome after selumetinib: A possible pathophysiological correlation? - Chelleri, Cristina; Scala, Marcello; De Marco, Patrizia; Traverso, Monica; Ognibene, Marzia; Bruno, Irene; Piccolo, Gianluca; Striano, Pasquale; Severino, Mariasavina; Zara, Federico; Diana, Maria Cristina; Pavanello, Marco (Frontiers in Pediatrics, 2023)
Neurofibromatosis type 1 (NF1) is a neurocutaneous syndrome caused by pathogenic variants in the NF1 gene, encoding a multidomain inhibitor of Ras activity. Thus, NF1 is considered a RASopathy and drugs targeting the RAS/mitogen-activated protein kinase (MAPK) pathway, such as the MAP kinase (MEK) 1/2 inhibitor Selumetinib, are promising therapeutic options to treat NF1-associated tumors, especially plexiform neurofibromas and optic way gliomas. However, surgical treatment is often required for NF1-related cerebrovascular manifestations, such as moyamoya syndrome (MMS). We report a case of an 8-year-old patient receiving Selumetinib at the dose of 25 mg/m2 orally 2 times a day as a treatment for many plexiform neurofibromas. He suffered from two close strokes and brain MRI revealed a severe cerebral vasculopathy consistent with MMS, with marked stenosis of both the internal carotid arteries. A two-step surgical revascularization procedure was performed, consisting of a direct by-pass with an encephalo-mio-synangiosis (EMS) followed by encephalo-duro-arterio-synangiosis (EDAS). Surprisingly, despite the surgical technical success, follow-up MRI revealed lack of the expected revascularization. Selumetinib is a powerful therapeutic option in the treatment of severe NF1-related tumors. However, our findings suggest that this drug may interfere with cerebral neovascularization in patients with MMS requiring surgical revascularization. This is supported by the crucial role of the Vascular-Endothelial Growth Factor (VEGF), whose signaling pathway involve MAPK, as promoter of the neovascularization. Our observations suggest to adopt an imaging surveillance strategy to prevent unfavorable surgical outcome in patients with NF1-associated MMS receiving Selumetinib, and that priority should be given to surgical revascularization.